TRAFFIC SUMMON SYSTEM - Tan, Ee Keng (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Traffic Summon System is a window application developed for the security staff. It is built to improve the features of the existing system. It allows user to check summonses, edit and delete summonses, add new summonses and generate reports. The main feature of this system is to pull out different reports for staff references. It helps reduce the time and complexity of tasks. This report describes the overall requirements, design, implementation and further work of the system. In the requirements, different types of method is use to gather information and classify them according to their priority. Then, the design is created based on the requirements. In the design process, different diagrams are drawn to allow us to view our system from multiple perspectives. Next, the system is implemented and walkthrough of every sub-module are discussed. Finally, discussion on further work on proposed system is stated for future system improvemen